2003
DOI: 10.1099/mic.0.26326-0
|View full text |Cite
|
Sign up to set email alerts
|

Distinct molecular mechanisms involved in carbon catabolite repression of the arabinose regulon in Bacillus subtilis

Abstract: The Bacillus subtilis proteins involved in the utilization of L-arabinose are encoded by the araABDLMNPQ-abfA metabolic operon and by the araE/araR divergent unit. Transcription from the ara operon, araE transport gene and araR regulatory gene is induced by L-arabinose and negatively controlled by AraR. Additionally, expression of both the ara operon and the araE gene is regulated at the transcriptional level by glucose repression. Here, by transcriptional fusion analysis in different mutant backgrounds, it is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
34
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 45 publications
3
34
0
Order By: Relevance
“…The operons involved in the catabolism of secondary carbon sources are as follows (the carbon sources in parentheses): gntRKPZ (gluconate), 16,35,36) xylAB (xylose), 9) iolABCDEFGHIJ (myo-inositol), 40,41,102) trePAR (trehalose), 25,47,103) galKT (galactose), 25) glpFK (glycerol), 33) glvARC (6-P--glucoside), 34) bglPH ( -glucoside), 26,27) yjlBCD-uxaC-yjmBCD-uxuA-yjmFexuTR-uxaBA (hexuronate), 25,48) xynPB ( -xyloside), 65) yxjC-scoAE-bdh ( -hydroxybutyrate), 25,49) ara-ABDLMNPQ-abfA (arabinose) 24,52,53) and abnA xsa (arabinose), 50) kdgRKAT (hexuronate), 25,42) and kduID (galacturonate). 43) The yxkF-msmX operon probably involved in the transport of unknown sugars has been found to be under CcpA-mediated CCR.…”
Section: Metabolic Network Mediated By Ccpamentioning
confidence: 99%
“…The operons involved in the catabolism of secondary carbon sources are as follows (the carbon sources in parentheses): gntRKPZ (gluconate), 16,35,36) xylAB (xylose), 9) iolABCDEFGHIJ (myo-inositol), 40,41,102) trePAR (trehalose), 25,47,103) galKT (galactose), 25) glpFK (glycerol), 33) glvARC (6-P--glucoside), 34) bglPH ( -glucoside), 26,27) yjlBCD-uxaC-yjmBCD-uxuA-yjmFexuTR-uxaBA (hexuronate), 25,48) xynPB ( -xyloside), 65) yxjC-scoAE-bdh ( -hydroxybutyrate), 25,49) ara-ABDLMNPQ-abfA (arabinose) 24,52,53) and abnA xsa (arabinose), 50) kdgRKAT (hexuronate), 25,42) and kduID (galacturonate). 43) The yxkF-msmX operon probably involved in the transport of unknown sugars has been found to be under CcpA-mediated CCR.…”
Section: Metabolic Network Mediated By Ccpamentioning
confidence: 99%
“…No significant differences in the levels of glucose repression were observed during early postexponential phase (t 4 ) ( Table 3). Previously, it has been shown that glucose repression of the araABDLMNPQ-abfA metabolic operon is mainly regulated by CcpA via binding to two catabolite responsive elements (CREs), one located between the promoter region of the operon and the araA gene and one located 2 kb downstream within the araB gene (11). Mutagenesis studies of B. subtilis revealed the CRE consensus sequence TGWAARCGYTWNCW (W ϭ A or T, R ϭ A or G, Y ϭ C or T, N ϭ any base) (14,18,38,41).…”
Section: Vol 186 2004 Regulation Of Arabinan Degradation In B Subtmentioning
confidence: 99%
“…The araR gene encodes the regulatory protein of L-arabinose metabolism in B. subtilis, negatively controlling the expression from the L-arabinose-inducible promoters of the ara genes (22,23). Additionally, the ara regulon is subjected to carbon catabolite repression by glucose and glycerol (11). The last gene of the L-arabinose metabolic operon, abfA, and the xsa gene located 23 kb downstream from the operon (32,40) (Fig.…”
mentioning
confidence: 99%
“…Therefore, AraR is thought to play a central role in the regulation of utilization of the multiple sugars in B. subtilis. It is noted that the L-arabinose catabolic and uptake genes are also subject to carbon catabolite repression, controlled by the cyclic AMP (cAMP)-dependent transcriptional regulator CRP in E. coli (24) and the LacI family transcriptional regulator CcpA in B. subtilis (25). These distinct regulatory systems are responsible for inhibition of L-arabinose utilization in the presence of D-glucose. Most strains of C. glutamicum tested cannot grow using L-arabinose as the sole carbon source owing to the lack of the pentose sugar utilization pathway (26).…”
mentioning
confidence: 99%